Utilization of the M3 Board Teaching Tool (Mean, Median, Mode) for Middle School Students in the Campus Teaching Program Batch 5 - Novita Sari; Mardiah Syofiana; Ristontowi Ristontowi; Risnanosanti Risnanosanti; Kashardi Kashardi; Rahmat Jumri; Masri Masri (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
SMP Negeri 7 Bengkulu City is one of the targets of the Campus Teaching Program Batch 5. This community service activity aims to demonstrate/utilize the M3 board teaching aid (Mean, Median, Mode) to 25 students of SMP Negeri 7 Bengkulu City, class VIII F. The method used is lectures and several group discussion activities. The results of this activity showed an increase in students' interest/motivation to learn numeracy by using the M3 board teaching aid (Mean, Median, Mode), as well as an increase in students' ability to solve questions related to the mean, median and mode. Thus, the use of M3 teaching aids (Mean, Median, Mode) is very important to be applied in the process of learning mathematics.